Study on laser cutting process of aluminum alloy explosion suppression material. Issue 2 (April 2021) - Zhou, Jingzhong; Zhang, Zhiwei; Niu, Fang; Lv, Jianjun
Abstract: Using laser cutting technology instead of the existing processing process to process aluminum alloy explosion-suppressing material mesh, the effect of laser output power, cutting speed and auxiliary blow pressure on the size of the seam and surface roughness is studied. Inverted optical microscope is used to characterize the shape and physical phase of the cut, and the composition content analysis of residue produced after vibration experiment is carried out using ICP-AES inductively coupled plasma emission spectrometer and CS-744 carbon sulfur analyzer. The results show that aluminum alloy explosion suppression material is prepared by laser cutting process, and the test parameters are laser output power 30W, cutting speed 200mm/s, auxiliary blow air pressure 0.7bar, and its cutting size and surface roughness are optimal. Ultrasonic cleaning can effectively remove patches from the surface of the material after cutting to achieve better surface quality requirements. Laser cutting process compared with the traditional mechanical cutting process has obvious advantages, smooth cutting, high processing accuracy, slag rate significantly reduced.